The tensioning process of ellipsoidal suspen-dome structures with considering the friction of cable-strut joints. (December 2021) - Fan, Xiongtao; Zhao, Zhongwei; Xu, Hao; Liu, Haiqing; Zhang, Ni; Wu, Xiufeng
Abstract: The friction between cable and cable-strut joints is a high nonlinear behavior which can cause the loss of cable force and then affect the mechanical behavior of integral structure during the construction and service phase. The ellipsoidal suspen-dome structures have been commonly utilized in practical engineering. Compared to the suspen-dome structures in spherical shape, the prestress loss of hoop cable is very different from the suspen-dome structures in ellipsoidal shape. To quantify the influence of friction force on the cable-strut joints of ellipsoidal suspen-dome structures, an iterative program for quantifying the friction force proposed by authors is integrated with tension compensation method. The influence of form coefficient and the connection stiffness, including axial stiffness and bending stiffness, are systematically investigated. The results indicated that the shape of upper grid structures has significantly influence on the loss of cable force. The friction can reduce the displacement of the whole structure and semi-rigid connection can increase the displacement of the whole structure, and the increase of both will lead to the increase of cable force loss. The friction will reduce the stress of radial rod, while semi-rigid connection will increase the internal force of radial rod. Both of them have little effect on the stress distribution of struts.